Application of advanced molecular to select the variety of Bitter gourd (Momordica charantia .L ) in Can Tho - Nguyen, Lang Thi; Bui, Hieu Chi; Nguyen, Loan Hong Thi; Nguyen, Phuoc Trong (International Journal of Environment, Agriculture and Biotechnology, 2023)
A study was conducted to evaluate the genetic variation in bitter ground to using SNP (single-nucleotide polymorphism) markers. Thirty -five primers showing reliable polymorphism were used .This paper mainly applies the molecular directive from the self-absorbed population of F6 of Cho Moi/Ben Tre. The Polymorphism on two SNP directives, TP1386 and TP 1877 with Bitter gourd on LG1. A wide variation was observed for morphological traits like the number of days to the first male flower anthesis (29.33–33.67), first female flower anthesis (30.5–38.6), fruit length (19.00–22.80 cm), fruit diameter (12.20–19.60 cm), and yield per plant (933.8–1147.9 g).According to the GGT map, it is easier to determine the genetic pattern of hybrids in the population compared to the genome of the parents in the F6 generation of the Cho Moi/Ben Tre . With 34 SNPs (single-nucleotide polymorphism) molecules directives on LG1, the genetic distance from 0-112. cM. The selected lines carried a superior homogeneity to the parent on the LG1. The result is 7 lines with F7 with 100% genes for hight yield the same with the father variety ( Ben Tre ), carrying hight yield. The seven lines selected are: 1(F2-2-1-7-1); 2(F2-8-17-2-2); 5(F2 -5-3-1-5); 7(F2-25-15-8-7); 10(F2-54-4-1-10; 35(F2-10-6-5-35); 36(F2-5-2-7-36). However, after evaluating F7 lines and comparing phenotypes and genotypes, there were only two lines: 2(F2-8-17-2-2); 7(F2-25-15-8-7)good appty for breeding and hight yield . Named line 7(F2-25-15-8-7) was designated HATRI 07KQ . DNA Sequence of HATRI 07KQ were submitted to GenBank .